Bridging Leadership and AI Adoption: The Mediating Role of Phenomenological Learning and the Moderating Effect of Digital Culture - Hashmi, Maria; Jovinda Percillia Ma’rifatul Umairoh; Mega Aprillia Pratamasari; Ogun Prayoga; Zaki Nur Hamam (International Journal of Economics, Business and Innovation Research, 2025)
This study investigates the role of transformational leadership, phenomenological learning, and digital culture in shaping the successful adoption of Artificial Intelligence (AI) within Indonesian organizations. Using a quantitative survey design, data were collected from 412 respondents across the service and manufacturing sectors. Structural Equation Modeling Partial Least Squares (SEM-PLS) was employed to test the hypothesized relationships. The findings reveal that transformational leadership significantly enhances phenomenological learning, which in turn positively influences AI adoption. Moreover, phenomenological learning mediates the relationship between transformational leadership and AI adoption, while digital culture strengthens the link between leadership and learning. These results highlight the importance of integrating phenomenological learning as a reflective and human-centered process in organizational digital transformation. The study contributes to theory by extending Phenomenological Learning Theory into technology adoption research and underscores the moderating role of digital culture in shaping organizational readiness. Practically, the findings suggest that leaders should foster reflective learning environments and cultivate adaptive digital cultures to accelerate inclusive and sustainable AI adoption.